VD_FINDINFO Arrêt / 2016 / 246 vom 21. März 2016 - VD Tribunal cantonal (2016)
MESURE RELATIVE AU MARCHÉ DU TRAVAIL, PROGRAMME D'EMPLOI TEMPORAIRE | 16 al. 2 let. c LACI, 59 LACI, 60 LACI, 64a al. 1 let. a LACI, 64a al. 2 LACI, 64a LACI